2016
DOI: 10.1007/s12311-016-0823-8
|View full text |Cite
|
Sign up to set email alerts
|

Defining Trends in Global Gene Expression in Arabian Horses with Cerebellar Abiotrophy

Abstract: Equine cerebellar abiotrophy (CA) is a hereditary neurodegenerative disease that affects the Purkinje neurons of the cerebellum and causes ataxia in Arabian foals. Signs of CA are typically first recognized either at birth to any time up to 6 months of age. CA is inherited as an autosomal recessive trait and is associated with a single nucleotide polymorphism (SNP) on equine chromosome 2 (13074277G>A), located in the fourth exon of TOE1 and in proximity to MUTYH on the antisense strand. We hypothesize that unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 52 publications
(82 reference statements)
1
12
0
2
Order By: Relevance
“…Cerebellar abiotrophy is inherited as an autosomal recessive trait and is associated with a single‐nucleotide polymorphism on chromosome 2 (13074277G>A), located in the 4th exon of TOE1 and in proximity to MUTYH on the antisense strand . This mutation results in loss of Purkinje neurons with secondary loss of the granular cell layer of the cerebellum . Signs can be recognized at birth or up to a few months of age and include ataxia, hypermetria, intention tremors, and lack of menace response .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cerebellar abiotrophy is inherited as an autosomal recessive trait and is associated with a single‐nucleotide polymorphism on chromosome 2 (13074277G>A), located in the 4th exon of TOE1 and in proximity to MUTYH on the antisense strand . This mutation results in loss of Purkinje neurons with secondary loss of the granular cell layer of the cerebellum . Signs can be recognized at birth or up to a few months of age and include ataxia, hypermetria, intention tremors, and lack of menace response .…”
Section: Discussionmentioning
confidence: 99%
“…35 This mutation results in loss of Purkinje neurons with secondary loss of the granular cell layer of the cerebellum. 25,36 Signs can be recognized at birth or up to a few months of age and include ataxia, hypermetria, intention tremors, and lack of menace response. 36 The prevalence of CA in a population of Arabian horses in South Africa was estimated to be 5.1%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the reports describing multiple cases of PCD have either suggested or established an autosomal recessive mode of inheritance through breeding studies, pedigree analysis or segregation analysis 3 15 17. Historically, PCD was considered a disease limited to the Arabian breed; however, a study showed that other breeds, which used Arabian progenitors as breeding stock, are also at risk of developing the disease 16.…”
Section: Discussionmentioning
confidence: 99%